FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN RISIKO (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014) - Syaifurakhman, Baredi; Laksito, Herry (Diponegoro Journal of Accounting, 2016)
The purpose of this study was to analyze the factors that influence the risk disclosure. The indicators used for the independent variable is the board size, liquidity, size of the audit committee, and the degree of leverage operation. While disclosure of risk as the dependent variable was measured by the method of content analysis. In addition, this study also uses firm size as a control variable.This study uses secondary data with the population of manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2014. The method used to determine the sample using purposive sampling, criteria of the sample is included in the company's manufacturing category. The sample consisted of 99 companies. The analytical method used is linear regression analysis.Hypothesis testing results show that the size of the board of directors and audit committee positively affects risk disclosure. While the degree of liquidity and leverage operation does not significantly affect the risk disclosure.